Larvicidal efficacy of Mundulea sericea (Leguminosae) plant extract against Anopheles gambiae (Giles) and Culex quinqefasciatus (Say) (Diptera: Culicidae) - Kiania, Nahashon Mugao; Mueke, Jones; Rukunga, Geoffrey; Anjili, Chris (My University, 2014)
Background: Anopheles gambiae is the main carrier for parasites that cause malaria and filariasis as well as viruses that cause yellow fever, dengue fever, dengue haemorrhagic fever, chikungunya and encephalitis. Culex quinqefasciatus on the other hand is the main vector for parasites that cause filariasis and the virus that cause encephalitis. Insecticide use to control these vectors has led to the development of mosquito resistance, environmental pollution, and undesirable effects on non-target organisms. Consequently, interest in insecticides of natural origin, particularly plant derived products, continues to receive much attention. Objective: To evaluate organic extracts of Mundulea sericea stem bark and leaves for efficacy against Anopheles gambiae and Culex quinqefasciatus larvae. Methodology: The plant parts were separated, dried and ground into fine powder and successively extracted using selected solvents. The dried extracts were dissolved in dimethylsulphoxide (DMSO) to prepare four to five different concentrations of each extract. The larvae were then exposed to concentrations ranging from 25 to 50,000 parts per million (ppm) of the extracts in an aqueous medium for 24 hrs at 25 - 30 °C. Results: Ethanol extract of the stem-bark displayed the most remarkable potential, with an LC90 of 188 ppm and 210 ppm for An. gambiae and Cx. cuinqefasciatus respectively. Leaf water extract displayed the highest LC50 of 45,000 ppm on Cx.quinqefasciatus and 9,000 ppm on An. gambiae. Comparatively, ethanol extracts from the stem-bark had significantly higher activity than that of the leaves. Conclusion: These findings suggest that bioactivity of phytochemicals from M. sericea plant varies significantly depending on solvent used in extraction and the part of the plant. Moreover, stem-bark extracts were more efficacious than leaf extracts. Overall, ethanol extracts of the root bark have the potential of being developed as larvicides for mosquito control.
doi:10.7392/openaccess.23050491
Keywords: Leguminosae; Mundulea sericea; Anopheles gambiae; Culex quinqefasciatus; larvicide